Caesarean scar pregnancy in the UK: a national cohort study. (5th June 2018) - Harb, HM; Knight, M; Bottomley, C; Overton, C; Tobias, A; Gallos, ID; Shehmar, M; Farquharson, R; Horne, A; Latthe, P; Edi‐Osagie, E; MacLean, M; et al.
Abstract : Objective: To estimate the incidence of caesarean scar pregnancy (CSP) and to describe the management outcomes associated with this condition. Design: A national cohort study using the UK Early Pregnancy Surveillance Service (UKEPSS). Setting: 86 participating Early Pregnancy Units. Population: All women diagnosed in the participating units with CSP between November 2013 and January 2015. Methods: Cohort study of women identified through the UKEPSS monthly mailing system. Main outcome measures: Incidence, clinical outcomes and complications. Results: 102 cases of CSP were reported, with an estimated incidence of 1.5 per 10 000 (95% CI 1.1–1.9) maternities. Full outcome data were available for 92 women. Management was expectant in 21/92 (23%), medical in 15/92 (16%) and surgical in 56/92 (61%). The success rates of expectant, medical and surgical management were 43% (9/21), 46% (7/15) and 96% (54/56), respectively. The complication rates were 15/21 (71%) with expectant, 9/15 (60%) with medical and 20/56 (36%) with surgical management. Discharge from care (median number of days) was 82 (range 37–174) with expectant, 21 (range 10–31) with medical and 11 (range 4–49) with surgical management. Conclusions: Surgical management appears to be associated with a high success rate, low complication rate and short post‐treatment follow up. Tweetable abstract: Surgery for CSP appears to be successful, with low complication rates and short post‐treatment follow up. Tweetable abstract: Surgery for CSP appears to be successful, with low complication rates and short post‐treatment follow up.